Collective labor agreement in respect of deciding the deciding the disbursement of a special raise to the private sector workers in the year 2013 = وزارة القوى العاملة والهجرة اتفاقية عمل جماعية بشأن تقرير علاوة خاصة للعاملين بالقطاع الخاص لعام 2013 / Collective Labor Agreement - Egypt. Collective Labor Agreement. (2025)
collective labor agreement in respect of deciding the deciding the disbursement of a special raise to the private sector workers in the year 2013 وزارة القوى العملة والهجرة اتفاقية عمل جماعية بشأن تقرير علاوة خاصة للعاملين بالقطاع الخاص لعام 2013